Estudio preliminar para la reproducción asexual in vitro de vainilla (Vanilla tahitensis) en diferentes medios de cultivos asépticos. - Loaiza Álvarez, Luis Hernán (2019)
Statistical efficiency is contrasted between two culture media with three different doses, Murashige and Skoog at 50 and 100 % with the doses of 100, 200 and 400 mg of glutamine, to determine the best concentration and dosage that can be applied in the development of plants in vitro vanilla. Week to week counts were carried out and observation of the development of the new outbreaks where the variables were: the color of explants, number of internodes and contaminated explants for which data were taken at 45 and 90 days. From the measured variables in the laboratory it was analyzed that the best concentration and dose in interaction was Murashige and Skoog to 100 % with glutamine in doses of 400 and 200 mg where the best development of the vanilla culture in vitro was reached. According to the hypothesis the application of different culture media and different doses of glutamine for vanilla if it influenced the development of vanilla plants.